Therapeutic Potentials of Bee Products for Treatment of COVID-19 - Ismail, Nur Faezah; Zulkifli, Muhammad Faiz; Wan Ismail, Wan Iryani (IIUM Medical Journal Malaysia, 2022)
The pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), or mostly known as COVID-19, has infected millions of people and led to a public health crisis. Various aspects including the economy and daily routine of life have also been severely affected. At the time being, treatment using previously FDA-approved antiviral such as hydroxychloroquine and remdesivir, as well as using convalescent plasma does not guarantee full recovery of COVID-19 infection. Thus, the search for effective treatment against COVID-19 is actively going on including using natural products. Bee products such as honey (with trehalulose sugar), propolis, royal jelly, bee pollen, and bee bread, are among the natural products that hold promises in attenuating COVID-19, either as an alternative source of the antiviral activity or to enhance the activity of current standard ward treatments. Besides being used in the human diet since ancient times, numerous pre-clinical and clinical studies have shown their pharmacological activities in improving general well-being as well as reducing the risk of developing various diseases. This review will consider a range of honey bee and stingless bee products and evaluate the evidence available for their therapeutic potential against COVID-19 infection. Here, we review the biological properties of bee products and evaluate the evidence available for their therapeutic potential in reducing the risk of developing COVID-19 as well as curing it.